The role of maladaptive cognitive schemas in the pathogenesis of comorbid affective disorders in persons with social anxiety and social phobias - Avramchuk, Oleksandr (Psychological Prospects Journal, 2023)
Purpose: to study the influence of cognitive maladaptive schemas on the severity of comorbid affective pathology, using the example of depressive symptoms in persons with social phobia.Methods. The search for previous studies was carried out using PubMed, Web-of-Science, and Research Gate services, focusing on research on social phobia and comorbid depressive conditions. The empirical study covered the indicators of samples with clinically significant signs of depressive symptoms according to DSM-5 criteria - the main group: 737 people with pronounced social anxiety and 582 people, the control group, without signs of social phobia. The results were evaluated according to the YSQ-S, SPIN, PHQ-9, and corresponding subscales of the SCL-90-R technique.Results. The statistical analysis results demonstrated that the level of severity of symptoms of depressive disorders and conditions in persons with social anxiety disorder is higher than in the control group. A significant difference was also demonstrated by indicators of the overall severity of symptoms and the index of symptomatologic distress. The analysis of actual early dysfunctional schemas showed significant differences (p